A First Course in Research Methods - Avwokeni, Arthur J. (Lagos, Nigeria University of Lagos Press, 2022)
This book is divided into four broad brush parts. Part 1 is devoted to address the meaning and practice of research. Part 2 provides a philosophical foundation to the theory of research. Part 3 builds on the philosophical foundation and seeks to apprise the reader of the various qualitative and quantitative approaches to research. Part 4 covers the elements of research design and analysis as a foundation to understand numerical procedures and their interpretation.
Includes bibliography, index
osc 06/02/2024
Loans
Keywords: Research Methods